Christensenella regulated by Huang-Qi-Ling-Hua-San is a key factor by which to improve type 2 diabetes - Pan, Tong; Zheng, Shujun; Zheng, Weiwei; Shi, Chao; Ning, Ke; Zhang, Qinghui; Xie, Yanbo; Xiang, Hongyu; Xie, Qiuhong (Frontiers in Microbiology, 2022)
There is a lot of evidence that oral hypoglycemic drugs work by affecting gut microbes, but the key strains responsible for this effect are not well known. Huang-Qi-Ling-Hua-San (HQLHS), composed of Astragalus Membranaceus, Ganoderma lucidum, Inonotus obliquus and Momordica charantia L., is a specially designed Chinese medicine formula to treat T2D (type 2 diabetes). In this study, a mouse model of T2D induced by high-fat diet and streptozotocin was used to explore the mechanism of HQLHS in improving hyperglycemia and hyperlipidemia through multiple rounds of animal experiments, such as HQLHS feeding, fecal microbiota transplantation (FMT), and live bacteria feeding, so as to explore the potential target intestinal flora in its hypoglycemic effect. Results show that such specific taxa as Bifidobacterium, Turicibacter, Alistipes, Romboutsia and Christensenella were identified to be preferably enriched by HQLHS and then assumed to be the target microbes. Herein, FMT was used to test if the up-regulated beneficial bacteria by HQLHS plays a therapeutic role. The strain Christensenella minuta DSM 22607 and the strain Christensenella timonensis DSM 102800 were selected to test the beneficial effect of Christensenella taxa on T2D. Diabetic animals supplemented with these strains showed the improvement in blood glucose and lipid metabolism, the promotion of GLP-1 secretion, the increase in antioxidant capacity, the inhibition of hepatic gluconeogenesis, the suppression of intestinal glucose absorption, the enhancement of intestinal barrier, reduced LPS-induced inflammation and the reduction of branched amino acids (BCAAs) content in the liver. Overall, these data demonstrate that Christensenella plays a beneficial role in T2D and is a target for the action of HQLHS therapy.